Adoption of Electric Vehicles in Car Sharing Market. Issue 1 (22nd September 2020) - Abouee‐Mehrizi, Hossein; Baron, Opher; Berman, Oded; Chen, David
Abstract : In this study, we examine whether it is optimal to use electric vehicles (EVs) in the car sharing market and investigate the environmental impact of pulling the EVs from the market. We develop a model consisting of a profit‐maximizing car sharing company (CSC) and a population of utility‐maximizing customers. The CSC sets the number of EVs, the number of fuel vehicles (FVs), and the rental price jointly to maximize its profit. Customers decide whether to use EVs, FVs, or public transportation to complete their trips considering the rental price. We show that it is optimal to use EVs only if the charging speed, the number of charging stations, and the range of EVs are high enough. Among these three conditions, the recharging speed is the most important and the number of charging stations is more important than the range of EVs. We also find that including EVs in the car sharing market may lead to a higher total emission when ignoring customers' other transportation choices (due to a lower rental price that results in a higher usage rate). Moreover, we consider the problem with the objective of maximizing the social welfare and find that when considering the environmental impact, governments should tax the CSC to induce a higher rental price and when ignoring this impact, they should subsidize the CSC to reduce the rental price. We demonstrate our results with the case study of Car2go. These results are in line with that the slow recharging speed may have been one of the contributing factors to that Car2go replaced EVs with FVs in San Diego.